Titanium dioxide nanoparticles as guardian against environmental carcinogen benzo[alpha]pyrene. - Anupam Dhasmana (Public Library of Science (PLoS), 2014)
Polycyclic aromatic hydrocarbons (PAH), like Benzo[alpha]Pyrene (BaP) are known to cause a number of toxic manifestations including lung cancer. As Titanium dioxide Nanoparticles (TiO2 NPs) have recently been shown to adsorb a number of PAHs from soil and water, we investigated whether TiO2 NPs could provide protection against the BaP induced toxicity in biological system. A549 cells when co-exposed with BaP (25 µM, 50 µM and 75 µM) along with 0.1 µg/ml,0.5 µg/ml and 1 µg/ml of TiO2 NPs, showed significant reduction in the toxic effects of BaP, as measured by Micronucleus Assay, MTT Assay and ROS Assay. In order to explore the mechanism of protection by TiO2 NP against BaP, we performed in silico studies. BaP and other PAHs are known to enter the cell via aromatic hydrocarbon receptor (AHR). TiO2 NP showed a much higher docking score with AHR (12074) as compared to the docking score of BaP with AHR (4600). This indicates a preferential binding of TiO2 NP with the AHR, in case if both the TiO2 NP and BaP are present. Further, we have done the docking of BaP with the TiO2 NP bound AHR-complex (score 4710), and observed that BaP showed strong adsorption on TiO2 NP itself, and not at its original binding site (at AHR). TiO2 NPs thereby prevent the entry of BaP in to the cell via AHR and hence protect cells against the deleterious effects induced by BaP.